2007
DOI: 10.1111/j.1742-6723.2007.00959.x
|View full text |Cite|
|
Sign up to set email alerts
|

Early computerized tomography accurately determines the presence or absence of scaphoid and other fractures

Abstract: Early CT scans show promise in the diagnosis of scaphoid and other fractures of the wrist and carpals. Further study is warranted to validate early CT in clinical scaphoid fracture as an alternative to other early advanced imaging, or plaster immobilization and 2 week review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 42 publications
(63 reference statements)
3
24
0
2
Order By: Relevance
“…Therefore, it can be assumed that early diagnosis and treatment planning cannot be assured if diagnosis relies on biplane radiography only. This is in concordance with recent reports supporting MDCT as a diagnostic modality of high diagnostic accuracy in scaphoid fracture detection [23][24][25][26] whereas in these reports radiography also was of limited value [23,25,27] . Stevenson et al [24] showed that using initial MDCT an occult scaphoid fracture can be ruled out with the patient returning to regular activity immediately.…”
Section: Resultssupporting
confidence: 92%
“…Therefore, it can be assumed that early diagnosis and treatment planning cannot be assured if diagnosis relies on biplane radiography only. This is in concordance with recent reports supporting MDCT as a diagnostic modality of high diagnostic accuracy in scaphoid fracture detection [23][24][25][26] whereas in these reports radiography also was of limited value [23,25,27] . Stevenson et al [24] showed that using initial MDCT an occult scaphoid fracture can be ruled out with the patient returning to regular activity immediately.…”
Section: Resultssupporting
confidence: 92%
“…These results did not change on sensitivity analysis with the four ED-based studies with LR+ of 23.0 (95% CI = 7.8 to 68) and LR-of 0.18 (95% CI = 0.16 to 0.34). 37,40,77,92 Ilica et al 90 used MRI exclusively as the criterion standard, but estimates of diagnostic accuracy did not differ from other studies using clinical examination, follow-up x-ray, or CT as the criterion standard. All of the studies except for one were prospective study designs, so sensitivity analysis was not conducted based on study design.…”
Section: Ctmentioning
confidence: 99%
“…[36][37][38][39][40] Among more recent, prospective ED-based studies that used MRI or bone scan as criterion standards, the prevalence of scaphoid fractures in patients with appropriate clinical suspicion and nondiagnostic initial x-rays ranges from 17% to 38%. [37][38][39][40] Therefore, based on these four prospective, ED-based diagnostic studies including a total of 274 patients, we think a reasonable pretest probability for adult ED patients with persistent wrist pain suspicious for a scaphoid fracture while still in the ED and normal ED x-rays is 25%. In other words, one in four of these patients will have a scaphoid fracture diagnosed on subsequent imaging.…”
Section: Prevalencementioning
confidence: 99%
See 2 more Smart Citations